Analisis Resiko Gagal Jantung pada Pasien Hipertensi di IGD Rumah Sakit Jember Klinik - Aji Permana, Roby; Agustin, Ratna Tri; Ekaprasetia, Feri (Journal of Pubnursing Sciences, 2025)
Background: Hypertensive patients experience an increase in systemic blood pressure, which places additional strain on the heart. This condition can increase the risk of heart failure. Objective: To assess the risk of heart failure in hypertensive patients treated at the Emergency Department of Jember Klinik Hospital. Method: This study employed a descriptive design using a cross-sectional approach. The study population consists of hypertensive patients at the Emergency Department of Jember Klinik Hospital. A total of 57 hypertensive patients who underwent examination at the Emergency Department of Jember Klinik Hospital between April and June 2024. The criteria of respondents were patients aged 30 to 74 years, composmentis, and able to communicate. The research instrument used the Framingham score to assess heart failure risk. Analysis statistic used analysis descriptive. Results: This study show that 6 respondents (10.5%) have a low risk, 17 respondents (29.8%) have a moderate risk, and 34 respondents (59.7%) have a high risk. Conclusion: The findings indicate that the majority of respondents are in the high-risk category for heart failure. Some risk factors need to be considered, including age, sex, systolic pressure, hypertension therapy, smoking, diabetes, and IMT so that respondents are able to control these.